Organic Nitrates: Past, Present and Future - Maria S. França-Silva; Camille M. Balarini; Josiane C. Cruz; Barkat A. Khan; Pabulo H. Rampelotto; Valdir A. Braga (Molecules, 2014)
Nitric oxide (NO) is one of the most important vasodilator molecules produced by the endothelium. It has already been established that NO/cGMP signaling pathway deficiencies are involved in the pathophysiological mechanisms of many cardiovascular diseases. In this context, the development of NO-releasing drugs for therapeutic use appears to be an effective alternative to replace the deficient endogenous NO and mimic the role of this molecule in the body. Organic nitrates represent the oldest class of NO donors that have been clinically used. Considering that tolerance can occur when these drugs are applied chronically, the search for new compounds of this class with lower tolerance potential is increasing. Here, we briefly discuss the mechanisms involved in nitrate tolerance and highlight some achievements from our group in the development of new organic nitrates and their preclinical application in cardiovascular disorders.